The production and marketing of South African Maize since 1910, with special reference to the years 1954 to 1966 - Brits, Rudolph Nieuwoudt (Rhodes University, Faculty of Commerce, Department of Economics, 1969)
From Introduction: There is no evidence available that maize was known in the old world in ancient times. Seeds of barley and wheat have been found in ancient near eastern sites, but never has there been any trace of maize at all. Furthermore, maize as a plant is not mentioned in the Bible, and neither Greek nor Chinese literature makes any reference to maize. There is, therefore, nothing that suggests that maize was known in the Old world before about 1492. However, at that time, Christopher Columbus returned with a report about a new grain called "Maiz". At a later date explorers visiting America found that maize was being grown and consumed by the Red Indians in places as far apart as Canada and Chile. The consensus of opinion is, therefore, that maize originated in America and was only subsequently imported into Europe. However, in a very excellent paper, Dr. M.D.W. Jeffreys comes to the very convincing conclusion that "Maize, a non-self-propagating American plant, was introduced to east African littorals before the Portuguese rounded the Cape and was seen by the Chinese navigators at Melinde Circa 1414"¦ Maize was brought to the Indian Ocean littorals by Arabs before 1400. Maize was brought into southern Africa by the Nguni by 1400 and later by the baVenda. Maize was introduced by the Dutch in 1658. There is no evidence that maize was introduced by the Portuguese. Irrespective of the exact date when maize was introduced into South Africa, it was only from the year 1840 that there was any real agricultural development in South Africa. At this date, all those who had participated in the Great Trek had more or less settled down, and substantial areas were planted with wheat, maize and oats.
Keywords: South Africa. Maize Board; Corn industry -- South Africa; Corn -- South Africa -- Marketing; Corn -- South Africa -- Marketing -- Government policy